FEATURES OF THE EDUCATIONAL REALITY OF ART TEACHER TRAINING TO THE IMPLEMENTATION OF NUSH REFORMS - Сегеда, Н.А. (SWorldJournal, 2022)
The publication considers the current attributes of modern professional training of music teachers as a holistic dynamic system of teaching, education, socialization and creative development aimed at solving the problem of culturally appropriate vocationa